User modelling for people with special needs. Issue 3 (19th August 2014) - Kurschl, Werner; Augstein, Mirjam; Burger, Thomas; Pointner, Claudia
Abstract : Purpose: The paper presents an approach where a novel user modeling wizard for people with motor impairments is used to gain a deeper understanding of very specific (touch-based and touchless) interaction patterns. The findings are used to set up and fill a user model which allows to automatically derive an application- and user-specific configuration for natural user interfaces. Design/methodology/approach: Based on expert knowledge in the domain of software/user interfaces for people with special needs, a test-case-based user modeling tool was developed. Task-based user tests were conducted with 7 users for the touch-based interaction scenario and with 5 users for the touchless interaction scenario. The participants are all people with different motor and/or cognitive impairments. Findings: The paper describes the results of different test cases that were designed to model users' touch-based and touchless interaction capabilities. In order to evaluate the tool's findings, experts additionally judged the participants' performance (their opinions were compared to the tool's findings). The results suggest that the user modeling tool could quite well capture users' capabilities. Originality/value: The paper describes the results of different test cases that were designed to model users' touch-based and touchless interaction capabilities. In order to evaluate the tool's findings, experts additionally judged the participants' performance (their opinions were compared to the tool's findings). The results suggest that the user modeling tool could quite well capture users' capabilities.